Bridging the Gap Between Individualized Inpatient Safety Planning and Postdischarge Efficacy. (May 2023) - Leonard, Jessica; Chiappetta, Laurel; Stark, Stacy; Mitchell, Ann M.
INTRODUCTION: Implementation of programs that increase both psychiatric patient education and their involvement in treatment programming can lead to positive outcomes postdischarge. Patients involved in programs focusing on skills, recovery, and that are individualized show a reduction in symptoms as well as an increase in engagement, treatment, and recovery posthospitalization. AIMS: This quality improvement project examines (1) the effectiveness of a safety planning group on an inpatient psychiatric unit for developing individualized safety plans, (2) the usefulness of the safety plans upon discharge, and (3) how helpful the patient found them. METHODS: A standardized safety plan was presented during 1-hour groups on an adult inpatient unit. Completed safety plans scored using a rubric to determine how patients individualized the content. One week postdischarge, patients were contacted to determine location and use of the safety plan since discharge. RESULTS: Patient's ( n = 124) safety plans were relatively individualized when compared to the standardized safety plan (mean [ SD ] = 32.85 [8.27] on a 44-point rating). Of those patients who were contacted postdischarge ( n = 76), 73 (96.1%) had a copy of their safety plan 1-week postdischarge while 28 (36.8%) reported using their safety plan since discharge. Many of the patients who used their safety plan reported that it was helpful ( n = 19; 67.9%). CONCLUSIONS: Developing a safety plan can be a helpful tool for individuals admitted to a psychiatric inpatient unit.